2020
DOI: 10.1119/10.0002067
|View full text |Cite
|
Sign up to set email alerts
|

How Perception of Being Recognized or Not Recognized by Instructors as a “Physics Person” Impacts Male and Female Students’ Self-Efficacy and Performance

Abstract: We discuss a study in a first year college introductory physics course for physical science and engineering majors that shows that women, on average, feel less recognized by their physics instructors than men as students who can excel in physics. We also discuss how this lack of perceived positive recognition pertaining to physics can adversely affect their self-efficacy and performance in the course. We recommend that physics instructors not be parsimonious in their praise of students and make a conscious eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Prior studies have shown that women are often underrepresented in many science, technology, engineering, and mathematics (STEM) courses and disciplines [1][2][3][4][5][6][7][8][9]. In addition, several studies have also reported gender disparity in students' performance in some STEM disciplines [10][11][12][13]. Some prior research suggests that individuals' course enrollment and performance in STEM can be influenced by their motivational beliefs such as self-efficacy, interest and identity in that domain [1][2][3]5,7,9,[14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that women are often underrepresented in many science, technology, engineering, and mathematics (STEM) courses and disciplines [1][2][3][4][5][6][7][8][9]. In addition, several studies have also reported gender disparity in students' performance in some STEM disciplines [10][11][12][13]. Some prior research suggests that individuals' course enrollment and performance in STEM can be influenced by their motivational beliefs such as self-efficacy, interest and identity in that domain [1][2][3]5,7,9,[14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…One study found that science faculty members in biological and physical sciences exhibit biases against female students by rating male students significantly more competent even when the accomplishments of the hypothetical female and male students were identical [ 42 ]. Thus the science identity of women in college science courses can be negatively impacted by their lower perceived recognition by others [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research shows that compared to men, women have lower perceived recognition as a "physics person" from peers and instructors [9][10][11][12][13], which can influence female students' decisions to leave the field [14]. In particular, if women believe that their instructors or peers do not see them as being capable of excelling in physics, it impacts their own beliefs about whether they can excel in physics [15]. Prior studies have also found that sense of belonging and self-efficacy in physics are closely intertwined [16].…”
Section: Introduction and Frameworkmentioning
confidence: 99%